THE NEED OF ENGLISH AT HIGHER EDUCATION - Yulia Hapsari; Esti Junining; Devinta Puspita Ratri (University of Kuningan, 2017)
Issues related to the need of English at higher education continue to be a discussion among scholars. Many believe that there is a positive relationship between English language skills of university students and their academic performance, and that English language skills are highly valued as a graduate attribute for employability. However, there are still few actions taken to gain information regarding which specific English language skills needed by educators and academic support staff. Universitas Brawijaya (UB) as one of the prominent higher education institutions in Indonesia is continuously taking actions to keep improving the quality of its graduates. One of the actions is to help its students to have a decent level of English language skills in order to help them to be ready to compete in work market that is going global. To reveal English language skills needed by bachelor graduates of the university as well as the reasons behind the need, sets of questionnaire were distributed to the educators in this case represented by the deans and academic support staff and the heads of academic support units both in the faculty and university level. The data from the questionnaires were then analyzed qualitatively. The findings of this study demonstrated that the educators need Reading and Writing skills more than the other two skills. This finding supports the idea that reading and writing skills are desperately needed to increase the number of publication in UB. Different from this result, the academic support staff perception on the need of English for the employees is on speaking skills. They think that speaking skills are the most needed skills for the employees to be able to handle the guest, and as a speaker of the units.Keyword: need of English, English language skills, higher education